2021
DOI: 10.3389/fcell.2021.684857
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin Induces Hepatic Stellate Cell Apoptosis Through Calpain-2/Ca2 +-Dependent Endoplasmic Reticulum Stress Pathway

Abstract: It has been reported that calpain/caspase-mediated apoptosis induced by endoplasmic reticulum stress (ERS) in hepatic stellate cells (HSCs) by previous studies. At present, the activation of HSC is an important cause of liver fibrosis, and the induction of HSC apoptosis plays an irreplaceable role in reversing liver fibrosis. Therefore, it is of great significance to explore mechanisms of action that can induce HSC apoptosis for the reversal of hepatic fibrosis and the clinical prevention and treatment of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…ER is an important Ca 2+ reservoir in cells. When cells are affected by exogenous compounds, ER stress occurs due to the disorder of calcium ion metabolism and function 38 . Therefore, ER stress induced by DNAJB9 might be partly mediated by DNAJB9's regulation of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…ER is an important Ca 2+ reservoir in cells. When cells are affected by exogenous compounds, ER stress occurs due to the disorder of calcium ion metabolism and function 38 . Therefore, ER stress induced by DNAJB9 might be partly mediated by DNAJB9's regulation of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…At high doses, tunicamycin increased ER stress markers but it reduced viability and migration of LX-2 cells. Tunicamycin is known as a potent ER stress inducer which can lead to HSC activation [40] but severe UPR with high dosage can also result in apoptosis [41,42]. One study showed that primary mouse HSCs which were cultured on plastic dish underwent activation from day fourth while UPR genes were induced just after 2 h. UPR was also seen earlier than the up-regulation of activation markers in freshly isolated HSCs from mice received single dose of CCl 4 , suggesting UPR is expressed early during HSC activation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Calpain-2 also plays a pivotal role in the tumor necrosis factor- (TNF-) α -induced autophagy in mouse hippocampal neurons [ 16 ]. Moreover, the tunicamycin-mediated calpain-2-dependent endoplasmic reticulum stress pathway leads to hepatic stellate cell apoptosis [ 17 ]. In addition, it has been reported that calpain-2 is involved in neuronal apoptosis induced by polybrominated diphenyl ether-153 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%